Key determinants of success for bumiputera entrepreneurs in small and medium-sized micro enterprises - Zaimah R.; Sharifah Ridzuah Syed Sayuthi; Sarmila, M.S.; Suraiya Ishak (Penerbit Universiti Kebangsaan Malaysia, 2025)
Bumiputera entrepreneurs play an important role in Micro, Small and Medium Enterprises (MSME) in the Malaysian economy. Therefore, the government has implemented a variety of initiatives and programs to increase the number of Bumiputra entrepreneurs. However, Bumiputera entrepreneurs still lag behind in the field of entrepreneurship, particularly in terms of sustainability and competitiveness. Although numerous studies have explored entrepreneurial success in general, there remains a limited number of empirical studies that specifically examine the critical success factors affecting Bumiputera entrepreneurs at the local level, especially in rural or semi-urban areas like Parit Sulong, Batu Pahat, Johor. Hence, this study aims to measure the level of success of Bumiputera entrepreneurs and determine the factors that influence their success in MSMEs in the aforementioned area. This study was conducted quantitatively using a questionnaire as a research tool. Purposive sampling techniques are used for data collection purposes. As a result, a total of 140 Bumiputera entrepreneurs were involved in this study. Descriptive analysis, Pearson correlation and multiple regression tests were applied for the purpose of answering the objectives of the study. Finding shows that Bumiputera entrepreneurs have a high overall score for success. The study also found that financial resources and financing, entrepreneurial skills, government support and technological innovation and adaptation have a significant relationship with the level of success of Bumiputera entrepreneurs. The main findings confirm that access to financial resources and financing, entrepreneurial skills and technological innovation and adaptation have an impact on entrepreneurs' success. The implication from this study summarizes that the factor of access to financial resources and financing still needs to be addressed to ensure that Bumiputera entrepreneurs' success is improved. Furthermore, the level of entrepreneurial skills supported by innovation and technological adaptation must be emphasized for Bumiputera entrepreneurs to survive in their businesses.